Investigation of coal pyrolysis tar of Aduunchuluun deposit - A, Ankhtuya; J, Namkhainorov; M, Battsetseg; S, Batbileg; D, Batkhishig; B, Purevsuren (Bulletin of the Institute of Chemistry and Chemical Technology, 2018)
The generated products of heating of coal in airless condition are hard residue, condensed liquid and gas. The condensed liquid product or tar is one of the most important product of pyrolysis. Therefore detailed investigation on pyrolysis of brown coal and it is tar studies provide basic theoretical knowledge for further thermal processing and application of coal. Have been determined main technical characteristics and elemental composition of the analytical sample of Aduunchuluun coal. The pyrolysis experiments have been performed at different heating temperatures (550-600oC) and determined the yields of pyrolysis products. The optimal heating temperature of pyrolysis of Aduunchuluun coal was chosen 500oC in which the yield of tar was higher (32%). The purified tar was subjected for FTIR analysis. Also the tar organic bases and organic acids are separated from the tar and the residual neutral fractions of pyrolysis tar were divided in to several fractions including aliphatic, aromatic and polar. And these fractions analyzed by GC/MS analysis and the determined most important organic substances are derivatives of benzene, naphtha-lene, phenols and alcohols. Адуунчулууны ордын нүүрсний пиролизын давирхайн судалгаа Хураангуй: Нүүрсийг агааргүй орчинд халуун задралд оруулахад хатуу, шингэн болон хийн бүтээгдэхүүн үүсэх ба чухал бүтээгдэхүүн нь шингэн бүтээгдэхүүн болох давирхай юм. Пиролизын давирхайн нарийвчилсан судалгаа нь тухайн нүүрсний цаашдын боловсруулалт болон хэрэглээнд онолын суурь мэдлэг болж өгдөг. Адуунчулууны ордын нүүрсний техникийн шинжилгээ (үнс, чийг, дэгдэмхий, илчлэг), элементийн бүрэлдэхүүнийг тодорхойлж уг ордын нүүрсийг халуун задралд (пиролизд 550-600 оС температурт) оруулж хий, шингэн (давирхайн задралын усны гарц 32%), хатуу бүтээгдэхүүний гарцыг тодорхойлж гарган авсан шингэн бүтээгдэхүүн давирхайн бүлгийн бүрэлдэхүүн, нил улаан туяаны спектрийн арга (НУТС), мөн янз бүрийн температурын хязгаарт нэрж гарцыг тогтоов. Мөн түүнчлэн Адуунчулууны ордын нүүрсний пиролизын давирхайн органик хүчил, суурийг нь салгаад үлдсэн саармаг нэгдэлд колонкон хроматограф ашиглан алифатик, ароматик, туйлт нэгдэл гэж ялган хийн хроматограф/масс спектрометр GC/MS-ийн багажит анализын аргаар нүүрсустөрөгчдийн найрлагыг нь тодорхойлоход бензол, нафталин, түүний уламжлал болон спиртүүд ихээр агуулагдаж байгааг тодорхойлов. Түлхүүр үг: пиролиз, давирхай, ароматик, туйлт, саармаг тос